Co(II)‐mediated effects of plain and plasma immersion ion implanted cobalt‐chromium alloys on the osteogenic differentiation of human mesenchymal stem cells. Issue 3 (2nd December 2014) - Schröck, Kathleen; Lutz, Johanna; Mändl, Stephan; Hacker, Michael C.; Kamprad, Manja; Schulz‐Siegmund, Michaela
Abstract Medical CoCr is one of the main alloys used for metal‐on‐metal prosthesis in patients with total hip arthroplasty. CoCr surfaces modified by nitrogen plasma immersion ion implantation (PIII) are characterized by improved wear resistance but also showed increased Co(II) ion release under in vitro conditions. For the first time, CoCr modified by nitrogen PIII was evaluated with regard to its effect on the osteogenic differentiation of MSC. The activity of alkaline phosphatase, the expression of the osteogenic genes Runt‐related transcription factor 2, osteopontin as well as integrin‐binding bone sialoprotein and the production of osteocalcin and hydroxyapatite were determined. The results of our study demonstrate that Co(II) ions released from the alloy affected the osteogenic differentiation of MSC. Distinct differences in differentiation markers were found between pristine and modified alloys for osteocalcin but not for integrin‐binding sialoprotein and hydroxyapatite. Interestingly, osteopontin was upregulated in naive and differentiated MSC by Co(II) ions and modified CoCr, likely through the induction of a cellular hypoxic response. The findings of this study contribute to a better understanding of possible risk factors with regard to a clinical applicability of surface modified CoCr implant materials. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:???–???, 2015.